2022
DOI: 10.1113/jp283051
|View full text |Cite
|
Sign up to set email alerts
|

On the haemodynamic consequence of the chemoreflex and muscle mechanoreflex interaction in women and men: two tales, one story

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Including matched groups of male and female participants, Wan et al (2022) found the mechanoreflex and chemoreflex interact to restrain peripheral hemodynamics in male adults, consistent with their prior published data (Wan et al, 2020). By contrast, these same reflex interactions in a group of healthy, normal weight, pre-menopausal, female adults potentiated peripheral vasodilatation.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…Including matched groups of male and female participants, Wan et al (2022) found the mechanoreflex and chemoreflex interact to restrain peripheral hemodynamics in male adults, consistent with their prior published data (Wan et al, 2020). By contrast, these same reflex interactions in a group of healthy, normal weight, pre-menopausal, female adults potentiated peripheral vasodilatation.…”
supporting
confidence: 86%
“…With this, it is also essential that we review these data through the lens of 'what's next?' The results obtained by Wan et al (2022) highlight that the same environmental stressors have the potential to elicit differing signs and symptoms in male vs. female adults. In the context of 'health' , as alluded by Wan et al (2022), it would be interesting to advance this work at altitude where exercise and chemoreflex activation coincide and where the majority of work has been conducted in a convenience sample of primarily young, healthy male adults.…”
mentioning
confidence: 85%
See 3 more Smart Citations